Scarcity Strategies and Price Promotions in Enhancing Consumer Purchase Intensity - Putriyandari, Rofily; Amran, Ali; Budi Hardjayanti, Nany (International Journal of Management Science and Information Technology, 2025)
Competition is fierce in the market today, and companies are always looking for new ways that they can stay ahead of the game when it comes to capturing consumer attention. Two classes of approaches are commonly employed: product scarcity and price promotion with the intention of inducing consumer purchase intention. Artificially creating scarcity by limiting availability or offer duration helps establish value in the mind of the consumer. In the meantime, price promotions, e.g., discounts and specials, lower price barriers and drive impulse purchasing. The synergy of these tactics would, it is imagined, boost the appeal of a product. But it is still unknown the combined influence on the purchase quantity and it requires some more researching. Knowledge about the effects of scarcity as well as price promotions on consumer behavior is important for marketers who need to design more effective marketing promotions and sell as much during buynow periods as possible. This research aims to investigate the impacts of product scarcity and price promotion on consumer purchase intensity. A Quantitative Study, Descriptive and Causal Designs Were Used and Multiple Regression Analysis Was Used to Vet the Relationship Among the Variables. The sample was comprised of 300 online shoppers in the areas of electronics and fashion. The investigation also found that both product scarcity and price promotions had significant impacts on purchase intensity and that the impact of product scarcity was a unimodal one. Furthermore, the relationship was found to be moderated by scarcity and promotion discounting effects on purchase intention were magnified. The findings indicate scarcity appeals can increase willingness to purchase and could be characterized as a double-edged sword where too much scarcity leads to falling returns. When used in combination, these tactics can work well for businesses to get the most from their marketing strategy.